2017
DOI: 10.1186/s12886-017-0605-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of strabismus in former preterm and full-term infants between 4 and 10 Years of age

Abstract: BackgroundLimited data exist collating most of the associated factors for strabismus in one analysis. The aim of this study was to assess the prevalence of strabismus and to analyse associated factors in former preterm and full-term infants.MethodsIn this cross-sectional study, 239 former preterm infants with gestational age (GA) ≤ 32 weeks and 264 former full-term born infants with GA ≥ 37 weeks underwent detailed ophthalmologic examination in the age of 4–10 years and perinatal data assessment for risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 34 publications
6
28
1
5
Order By: Relevance
“…This phenomenon is frequently reported in systemic disorders, such as cardiovascular disease, obesity and diabetes 5–8. Several studies have shown that newborns with low BW show an increased risk of developing ocular comorbidities,9 higher myopic refractive error,10 astigmatism11 and visual dysfunction12–15 in childhood, particularly in infants with extreme prematurity and extreme low BW.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is frequently reported in systemic disorders, such as cardiovascular disease, obesity and diabetes 5–8. Several studies have shown that newborns with low BW show an increased risk of developing ocular comorbidities,9 higher myopic refractive error,10 astigmatism11 and visual dysfunction12–15 in childhood, particularly in infants with extreme prematurity and extreme low BW.…”
Section: Introductionmentioning
confidence: 99%
“…When the other study without confounder adjustment (Fieβ A et al. ) was removed, the combined result of the remaining studies was 1.46 (95% CI: 1.32–1.60). Then, we omitted the two studies, and the result had hardly changed (1.46; 95% CI: 1.32–1.61), which demonstrated the primary results were robust and stable.…”
Section: Resultsmentioning
confidence: 99%
“…After excluding the study conducted by Pathai et al (2010) and his colleagues, where no confounding factor was adjusted, we yielded a pooled OR of 1.45 (95% CI: 1.32-1.61). When the other study without confounder adjustment (Fieb A et al 2017) was removed, the combined result of the remaining studies was 1.46 (95% CI: 1.32-1.60). Then, we omitted the two studies, and the result had hardly changed (1.46; 95% CI: 1.32-1.61), which demonstrated the primary results were robust and stable.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…It has been reported that prematurity and maternal smoking during pregnancy are associated with a higher risk of paediatric esotropia and exotropia [9]. Furthermore, strabismus was associated with gestational age, hyperopic refractive error and astigmatism [10]. Esotropia, with lower gestational age and a heavier placenta; exotropia, with a maternal history of previously treated hypertension and maternal use of recreational drugs during early pregnancy [11].…”
Section: Discussionmentioning
confidence: 99%